2014
DOI: 10.3409/fb62_2.143
|View full text |Cite
|
Sign up to set email alerts
|

Are Chondroclasts and Osteoclasts Identical?

Abstract: Brief characteristics of cells termed osteoclasts and chondroclasts are outlined and reasons to consider them as the same cell type, able to resorb calcified matrix, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In calcified cartilage resorption, osteoclasts are sometimes referred to as “chondroclasts,” due to the substrate on which they are working. Chondroclasts and osteoclasts appear to be the same cell type based on shared features and regulatory mechanisms and osteoclasts’ capacity for resorbing mineralized cartilage (Helfrich 2003; Włodarski et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In calcified cartilage resorption, osteoclasts are sometimes referred to as “chondroclasts,” due to the substrate on which they are working. Chondroclasts and osteoclasts appear to be the same cell type based on shared features and regulatory mechanisms and osteoclasts’ capacity for resorbing mineralized cartilage (Helfrich 2003; Włodarski et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial cells are accompanied by perivascular cells and pericytes, and by mononuclear cells expressing cathepsin B, termed septoclasts (5,33,35,36). Calcified septa are resorbed by multinuclear cells called osteoclasts or chondroclasts (33,37,38). The osteoclasts extend their cell processes into the cartilage matrix and entrap the calcified cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…TEM observation showed that multinucleated chondroclasts degraded mineralized cartilage matrix with no apposition of bone tissue by ruffled borders and clear zones. Similarities and differences between multinucleated osteoclasts and chondroclasts have been discussed (Wlodarski et al, 2014). From an ultrastructural standpoint in dog mandibular condylar cartilage, Sasaki et al (1996) insisted that preosteoclastic (prechondroclastic) multinucleated cells developed neither ruffled borders nor clear zones in the cartilage matrix, but once the bone layer had been deposited on the remaining cartilage, these structures formed, that is, chondroclasts cannot resorb just mineralized cartilage matrix by ruffled borders.…”
Section: Development Of the Gonial Bone With Ossification Of The Malleusmentioning
confidence: 99%